2019
DOI: 10.3390/cancers11121916
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Droplet Digital PCR Is a Powerful Tool for Detection of BRAF and TERT Mutations in Papillary Thyroid Carcinomas

Abstract: We examined the utility of microfluidic digital PCR (dPCR) for detection of BRAF and TERT mutations in thyroid tumors. DNA extracted from 100 thyroid tumors (10 follicular adenomas, 10 follicular cancers, 5 medullary cancers, and 75 papillary thyroid cancer (PTC) were used for detection of BRAF and TERT mutations. Digital PCRs were performed using rare mutation SNP genotyping assays on QuantStudio 3D platform. In PTCs, BRAFV600E was detected by dPCR and Sanger sequencing in 42/75 (56%) and in 37/75 (49%), resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…The BRAFV600E mutation was undetectable by ARMS but detectable by ddPCR in 13 patients. Among the 329 PTC patients, the ratio of BRAFV600E alleles in 165 cases was less than 10%, which is usually beyond the range detected by the first-generation gene detection technology(26,41).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The BRAFV600E mutation was undetectable by ARMS but detectable by ddPCR in 13 patients. Among the 329 PTC patients, the ratio of BRAFV600E alleles in 165 cases was less than 10%, which is usually beyond the range detected by the first-generation gene detection technology(26,41).…”
Section: Discussionmentioning
confidence: 96%
“…Detection of the BRAFV600E mutation by ddPCR has been demonstrated in melanoma samples and pancreas fine needle aspiration (FNA) specimens(23-25). A recent study showed that mutant BRAFV600E was detected in 56%(42/75) of PTC tumors by ddPCR and that the ratio of mutant/total BRAF alleles varied from 4.7% to 47.5%, suggesting that ddPCR detection of the BRAFV600E mutation should be a suitable assay for the molecular-based stratification of prognosis in patients with PTC(26).…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidic digital PCR analyses were performed on a QuantStudio™ 3D Digital PCR System (Life Technologies, Carlsbad, CA, USA) as per the previously published protocol [29]. The rare mutation SNP genotyping assays for BRAFV600E (Fluorescein-FAM) which was multiplexed with an assay for the detection of wild-type BRAF (2 -chloro-7 phenyl-1,4-dichloro-6-carboxy-fluorescein-VIC) were synthesized by Thermo Fisher Scientific.…”
Section: Detection Of Brafv600 Mutation By Digital Pcrmentioning
confidence: 99%
“…We established a protocol to detect BRAFV600E in thyroid cancer samples by microfluidic digital PCR and described this technique in a previously published study [29]. In the present study, we applied a similar approach and in addition, used a co-amplification at COLD-PCR prior to digital PCR.…”
Section: Combination Of Microfluidic Digital Pcr With Cold-pcr Increamentioning
confidence: 99%
“…In the first paper, Ylli et al analyzed the utility of digital PCR technique in detecting BRAF V600E and TERT promoter mutations ( C228T and C250T ) in thyroid cancer tissue samples. Interestingly, microfluidic digital PCR allowed for specific, sensitive and rapid detection of BRAF V600E and TERT C228T mutations in thyroid tissue samples and could be used for quantification of mutant alleles in an easy and cost-effective manner [ 6 ]. In the second paper, Capitoli et al applied, for the first time, Matrix-Assisted Laser Desorption/Ionization (MALDI) Mass Spectrometry Imaging (MSI) on real thyroid Fine Needle Aspirations (FNAs) to test its possible complementary role in routine cytology in the diagnosis of thyroid nodules.…”
mentioning
confidence: 99%